PELAKSANAAN PASAL 22 PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 PADA PEMBUATAN AKTA TANAH DI KANTOR PEJABAT PEMBUAT AKTA TANAH (PPAT) - Michell eko Hardian (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2020)
Land Deed Makers Officer is a general official who is authorized to make a deed concerning legal regulations concerning land rights or ownership rights over a unit of flats, this stipulates in Government Regulation Number 37 of 1998 concerning PPAT Position Regulations, specifically in article 22 which states that : Deed of Acting Author of Land Deed Must be read / Explained its contents to the parties attended by at least 2 (two) participants before it was immediately signed by the parties, representatives and PPAT conducted before the Land Deed was made seen. Pursuant to the regulation on the making of the Deed of Transition on Land there is still a PPAT that does not apply. Article 22 of the Government Regulation Number 37 of 1998 according to the procedure as mandated by the legislation requested, is needed to make the writer as a researcher who wants to reproduce and reveal whether there is no article 22 PP 37 below is approved according to the agreed regulationsKeywords: Effectiveness of PPAT, Implementation of PP 37/1998